Outcomes in Adult Sinonasal Rhabdomyosarcoma. (14th March 2017) - Stepan, Katelyn; Konuthula, Neeraja; Khan, Mohemmed; Parasher, Arjun; Del Signore, Anthony; Govindaraj, Satish; Genden, Eric; Iloreta, Alfred
Abstract : Objective: To describe patient demographics, histology, treatment modalities, and survival associated with adult sinonasal rhabdomyosarcoma. Study Design: Retrospective review of a national database. Setting: Tertiary medical center. Subjects and Methods: Patient demographics, tumor histology, treatment modalities, and survival trends were examined for patients aged ≥18 years who were diagnosed with sinonasal rhabdomyosarcoma between 2004 and 2013 with the National Cancer Database. Kaplan‐Meier analysis and the log‐rank tests were performed to determine the unadjusted association between overall survival and various patient and disease characteristics. Results: A total of 186 patients were identified; 5‐year overall survival was 28.4%. Over half of patients were between 18 and 35 years old at diagnosis (53.8%), which was associated with improved 5‐year overall survival over patients >35 years old (31.9% vs 24.4%, P =. 014). Alveolar sinonasal rhabdomyosarcoma was most common (66.7%). There was no statistical difference in 5‐year overall survival between alveolar and embryonal subtypes (30.5% vs 41.6%, P >. 05). Metastatic disease was present in 27.7% of patients and was associated with worse 5‐year overall survival (14.7% vs 33.9%, P <. 0001). The majority of patients were treated with chemotherapy with adjuvant radiation (49.5%). A quarter of patients were treated with surgery plus chemoradiation (25.8%). Conclusion: We present the largest analysis of adult sinonasal rhabdomyosarcoma using a standardized national based database. Adult sinonasal rhabdomyosarcoma has a very poor prognosis independent of histologic subtype. The small number of surgical cases limits the ability of the analysis to accurately compare treatment with chemoradiation with and without surgery.